Vimentin undergoes liquid–liquid phase separation to form droplets which wet and stabilize actin fibers - Arkaprabha Basu; Tommy Krug; Benjamin du Pont; Qiaoling Huang; Sijie Sun; Stephen A. Adam; Robert D. Goldman; David A. Weitz (Proceedings of the National Academy of Sciences, 2025)
The cytoskeleton is composed of F-actin, microtubules, and intermediate filaments (IFs). Vimentin is one of the most ubiquitous and well-studied IFs. It is involved in many activities including wound healing, tissue fibrosis, and cancer metastasis, all of which require rapid vimentin IF assembly. In this paper, we report that vimentin forms liquid condensates which appear to enable rapid filament growth. Given the transient nature of these droplets, we focus on properties of vimentin-Y117L, which has a point mutation that leads to formation of condensates but not IFs, enabling us to study these droplets in detail. The droplets dissolve under 1,6-Hexanediol treatment and under decreasing concentration, confirming that they are liquid, and phase separated. These condensates extensively wet actin stress fibers, rendering them resistant to actin-binding drugs and protecting them from depolymerization. We show similar behavior occurs in wild-type vimentin during its assembly into filaments.